TFEU Clause 346 Application to Defence and Security Public Procurement - Kuzminskas, Vilius (Teisė, 2018)
The article discloses in the Treaty of Function of European Union clause 346 fixed exclusion, that provides ability for the EU member states to depart from the mandatory application of European law for the procurement in defense area. Point of view to this exclusion of the European Commission, European Court of Justice and procurement in defense area doctrine are analyzed and exclusion interpretations reasonableness problems are disclosed.